1994
DOI: 10.1080/01904169409364791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil application of cadmium contaminated lime on soil cadmium distribution and cadmium concentration in strawberry leaves and fruit

Abstract: Heavy metal environmental pollution which occurs as a result of lime contaminated with cadmium (Cd) poses a potential health hazard. This investigation was undertaken to study uptake of Cd by strawberry plants grown in soil amended with three different sources and two different rates of industry waste lime containing 3.4, 14.3, and 60.0 mg Cd/kg, respectively. The effects of Cd applied to the soil were investigated, including its distribution in the soil and effect on Cd concentration in strawberry cv. Senga S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This species, tolerant of acid soils, might be expected to easily take up and accumulate Cd from soil. However, only a few studies have examined Cd uptake by strawberries grown in Cd-contaminated and/or noncontaminated soils (Cie~lifiski et al, 1994;Szteke et al, 1989). There is, therefore, a need for additional study carried out under controlled conditions to better understand strawberry growth in heavy metal contaminated soils.…”
Section: Introductionmentioning
confidence: 99%
“…This species, tolerant of acid soils, might be expected to easily take up and accumulate Cd from soil. However, only a few studies have examined Cd uptake by strawberries grown in Cd-contaminated and/or noncontaminated soils (Cie~lifiski et al, 1994;Szteke et al, 1989). There is, therefore, a need for additional study carried out under controlled conditions to better understand strawberry growth in heavy metal contaminated soils.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that lower concentrations of Cd stimulated increase of sorghum height, which may be related to the certain resistance of the sorghum genus plant. The higher concentrations hindered their development; explanations behind the restraining impact of substantial metals to plant development were presumably due to: [A] A progression of physical and chemical responses between the overabundance substantial metal and soil parts which changes soil properties, along these lines influencing soil fruitfulness [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…These phenolic compounds have been shown to possess beneficial effects for human health (Hannum, 2004). However, the growth of strawberry plants and the quality of the fruit may be influenced by a number of environmental factors such as temperature (Wang and Camp, 2000), salinity (Jamalian et al, 2008), and the presence of heavy metals (Cieslinski et al, 1994). It has been reported that cadmium (Cd) significantly affects the growth and yield of strawberry (Cieslinski et al, 1996).…”
mentioning
confidence: 99%
“…It has been reported that cadmium (Cd) significantly affects the growth and yield of strawberry (Cieslinski et al, 1996). Cd is easily taken-up by strawberry plants and accumulated in all organs, including the roots, leaves, stems, and fruits (Cieslinski et al, 1994).…”
mentioning
confidence: 99%